2005
DOI: 10.1016/j.cell.2005.08.037
|View full text |Cite
|
Sign up to set email alerts
|

GPCR Signaling Is Required for Blood-Brain Barrier Formation in Drosophila

Abstract: The blood-brain barrier of Drosophila is established by surface glia, which ensheath the nerve cord and insulate it against the potassium-rich hemolymph by forming intercellular septate junctions. The mechanisms underlying the formation of this barrier remain obscure. Here, we show that the G protein-coupled receptor (GPCR) Moody, the G protein subunits G alpha i and G alpha o, and the regulator of G protein signaling Loco are required in the surface glia to achieve effective insulation. Our data suggest that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
350
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 234 publications
(361 citation statements)
references
References 49 publications
(44 reference statements)
10
350
0
1
Order By: Relevance
“…Invertebrate axons are insulated from their salt-rich environment through a glial-dependent BBB, which plays a crucial role in electrical and chemical insulation (Auld et al, 1995;Baumgartner et al, 1996;Bainton et al, 2005;Schwabe et al, 2005). Ultrastructural studies have demonstrated SJs between perineurial glial cells and inner glial cell membrane to form the structural basis of BBB of some insects (Carlson et al, 2000).…”
Section: Sjs As Molecular Barriers: a Common Theme In Axonal Insulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Invertebrate axons are insulated from their salt-rich environment through a glial-dependent BBB, which plays a crucial role in electrical and chemical insulation (Auld et al, 1995;Baumgartner et al, 1996;Bainton et al, 2005;Schwabe et al, 2005). Ultrastructural studies have demonstrated SJs between perineurial glial cells and inner glial cell membrane to form the structural basis of BBB of some insects (Carlson et al, 2000).…”
Section: Sjs As Molecular Barriers: a Common Theme In Axonal Insulationmentioning
confidence: 99%
“…Recent analyses of SJs in Drosophila show the presence of a number of proteins that are enriched at or associated with SJs (for review, see Banerjee et al, 2006). Interestingly, most of these proteins are localized at the epithelial SJs, only Neurexin IV (Nrx IV) and Gliotactin are reported to be functional in the peripheral glia, whereas Moody and Loco are required in the surface glia to achieve effective insulation of the CNS Schwabe et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Surface glia ensheath the brain and play a role in the formation of the blood-brain barrier. Cortex glia surround neurons and neuroblasts, while neuropile glia compartmentalize the neuropile, forming axon tracts for neurites (Chotard et al 2005;Pereanu et al 2005;Schwabe et al 2005). In addition, another subset of glia, the retinal basal glia, are born in the optic stalk and migrate into the eye imaginal disc (Choi and Benzer 1994;Rangarajan et al 1999).…”
mentioning
confidence: 99%
“…Disruption of loco gene function leads to multiple defects during development in Drosophila (Granderath et al 1999;Pathirana et al 2001;Yu et al 2005). In loco loss-of-function mutant embryos, failure of glial differentiation leads to improper ensheathing of neuronal axons and, consequently, the blood-brain barrier is disrupted (Granderath et al 1999;Schwabe et al 2005). Biochemical studies in Drosophila embryos have shown that Loco regulates these processes by direct physical interaction with G-protein subunits (Schwabe et al 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation